(untitled) (Bangladesh Journal of Microbiology, 2016)
A total of 50 isolates of Escherichia coli obtained from healthy adult human subjects were studied and tested for possible presence of efflux mechanism in resistance determination and possible correlation of plasmids with resistance.Minimal inhibitory concentration (MIC) of the antibiotics amoxicillin, azithromycin, ciprofloxacin, chloramphenicol and tetracycline were determined by agar dilution method with or without the H+/K+ proton pump inhibitor omeprazole. Plasmids were extracted by rapid alkaline plasmid extraction method and analyzed by agarose gel electrophoresis. Many strains showed 5 10 fold reduction of MIC values in the presence of omeprazole; a few strains showed up to 100-fold MIC reduction. Plasmid analysis of these 50 isolates revealed the presence of both plasmidless and plasmid containing strains, the latter with plasmid number varying from one to seven. However, the plasmids apparently had no relationship with high level antibiotic tolerance as indicated by the observation that some plasmidless strains had very high MIC values, while other strains containing several plasmids had very low MIC. Decrease in MIC in the presence of omeprazole apparently indicates existence of an efflux mechanism. Evidence of the efflux of ethidium bromide was noted in some strains that had been grown in ethidium bromide containing agar plate with and without omeprazole. These results suggest that reduction of MIC caused by omeprazole may be related to possible inhibition of efflux pump activity by omeprazole in the isolates studied. Bangladesh J Microbiol, Volume 30, Number 1-2,June-Dec 2013, pp 55-59